Immunotherapeutic Targeting of GPC3 in Pediatric Solid Embryonal Tumors - Ortiz, Michael V.; Roberts, Stephen S.; Glade Bender, Julia; Shukla, Neerav; Wexler, Leonard H. (Frontiers in Oncology, 2019)
Glypican 3 (GPC3) is a heparan sulfate proteoglycan and cell surface oncofetal protein which is highly expressed on a variety of pediatric solid embryonal tumors including the majority of hepatoblastomas, Wilms tumors, rhabdoid tumors, certain germ cell tumor subtypes, and a minority of rhabdomyosarcomas. Via its heparan sulfate side chains, GPC3 activates the canonical Wnt/β-catenin and insulin-like growth factor signaling pathways, which are frequently overexpressed in these malignancies. Loss of function mutations in GPC3 lead to Simpson-Golabi-Behmel Syndrome, an X-linked overgrowth condition with a predisposition to GPC3-expressing cancers including hepatoblastoma and Wilms tumor. There are several immunotherapeutic approaches to targeting GPC3, including vaccines, monoclonal antibodies, antibody-drug conjugates, bispecific antibodies, cytolytic T lymphocytes, and CAR T cells. These therapies offer a potentially novel means to target these pediatric solid embryonal tumors. A key pediatric-specific consideration of GPC3-targeted immunotherapeutics is that GPC3 can be physiologically expressed in normal tissues during the first year of life, particularly in the liver and kidney. In summary, this article reviews the current evidence for targeting childhood cancers with GPC3-directed immunotherapies.